PERANCANGAN UI/UX PADA WEBSITE MEDISOL DENGAN METODE USER CENTERED DESIGN - Pratiwy aggraeny puspita sari; Mohammad Fajar; Arianti (KHARISMA Tech, 2023)
This study aims to redesign the UI/UX of the Medisol website using the User Centered Design (UCD) method to suit user needs. The research data was collected through interviews with 30 respondents based on task scenarios to calculate the three main factors in usability testing, namely effectiveness, efficiency and user satisfaction factors. The initial evaluation of the system before the design improvement shows the effectiveness parameters of 84%, efficiency of 73% and user satisfaction of 82%. The usability level of the system in the early stages is 80%. Based on this evaluation, a prototype was redesigned which took into account user input such as a more responsive display of drug additions and vacancies, availability of information on procedures for adding drugs, contact us/email information placed in the header, green color on the dashboard, and boxes/tables. information on a clickable dashboard. The results of usability testing in this second stage obtained the value of the effectiveness parameter of 100%, the efficiency factor of 99% and the user satisfaction factor with a score of 96%. The resulting usability value increased to 98%. This shows that the UI/UX redesign of the Medisol website increased the usability value by 18%.